Determining Customer Satisfaction and Loyalty in Banking sector of Karachi, Pakistan (KASBIT Business Journal, 2020)
This paper aims to assess the influence of perceived price fairness, service quality, and service convenience on customer satisfaction and customer loyalty for the banking sector of Karachi, Pakistan. In addition to that, the influence of customer satisfaction is assessed on customer loyalty in the banking sector context. To test the proposed relationships, the data were collected from 425 account holders. The results of the analysis revealed that dimensions of service quality such as employees’ behavior and tangibility have a significant influence on customer satisfaction and loyalty. On the other hand, information technology does not have a significant influence on customer satisfaction and loyalty. Moreover, the analysis revealed that perceived price fairness also asserts significant positive influence on customer satisfaction and loyalty. Among the dimensions of service convenience (benefit convenience) significantly impact, whereas, transaction convenience and benefit convenience failed to exert any impact on customer loyalty. Based on the results of data analysis, it has been suggested that bank executives should put more effort to ensure the provision of quality services to their customers. In addition to that, they should make promises that are feasible within the given resources. Moreover, employees should be provided with extensive training that enables them to provide uniform, standardized, and quality services to baking customers.
Keywords: Service quality; service convenience; perceived price fairness; customer satisfaction; customer loyalty